Location and natural history are key to determining impact of the 2021 atmospheric heatwave on Pacific Northwest rocky intertidal communities - Miner, C. Melissa; Berry, Helen D.; Bohlmann, Heath; Dethier, Megan N.; Fradkin, Steven C.; Gaddam, Rani; Raymond, Wendel W.; Raimondi, Peter T. (Frontiers in Marine Science, 2025)
IntroductionIn late June 2021, the Pacific Northwest region of the United States and Canada experienced an unprecedented atmospheric heatwave that co-occurred with one of the lowest day-time tide series of the year. Several consecutive days of air temperatures 10-20°C above normal, coupled with mid-afternoon low tides proved deadly for many rocky intertidal organisms, which live at the margin of land and sea.MethodsTo assess short (weeks) and longer-term (1 year) impacts of the heatwave on rocky intertidal communities, we used long-term monitoring data collected annually at 16 sites throughout Washington State.Results and discussionOur findings indicate that impacts were most severe at sites within the Salish Sea region of WA, where peak low tides occurred during the hottest, mid-afternoon hours. Focal species assemblages at Olympic coast sites, where low tides occurred in the morning, were largely spared. In addition, while the heatwave was associated with substantial short-term changes in acorn barnacle, rockweed, and California mussel assemblages, lasting impacts (1 year) were only observed in the mussel assemblage at the one Salish Sea site where this species is common. These findings will aid in forecasting both short-term and longer lasting impacts of future heatwave events and help direct potential mitigation efforts to regions and species assemblages where impacts will likely be greatest.